2016
DOI: 10.1038/srep19137
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV inhibits microglia activation via glucocorticoid receptor mediated signaling pathway

Abstract: Inhibition of microglia activation may provide therapeutic treatment for many neurodegenerative diseases. Astragaloside IV (ASI) with anti-inflammatory properties has been tested as a therapeutic drug in clinical trials of China. However, the mechanism of ASI inhibiting neuroinflammation is unknown. In this study, we showed that ASI inhibited microglia activation both in vivo and in vitro. It could enhance glucocorticoid receptor (GR)-luciferase activity and facilitate GR nuclear translocation in microglial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…As disclosed in our previous study, total astragalosides alleviated neuroinflammation via the inhibition of iNOS and other inflammatory cytokines in mice with experimental autoimmune encephalomyelitis (25). Moreover, astragaloside IV, one of the saponin molecules within total astragalosides, has been shown to inhibit microglial activation via the glucocorticoid receptor-mediated signaling pathway (20). In this study, we demonstrated that another saponin molecule, ISO I, within total astragalosides, also inhibited the activation of microglia.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As disclosed in our previous study, total astragalosides alleviated neuroinflammation via the inhibition of iNOS and other inflammatory cytokines in mice with experimental autoimmune encephalomyelitis (25). Moreover, astragaloside IV, one of the saponin molecules within total astragalosides, has been shown to inhibit microglial activation via the glucocorticoid receptor-mediated signaling pathway (20). In this study, we demonstrated that another saponin molecule, ISO I, within total astragalosides, also inhibited the activation of microglia.…”
Section: Discussionsupporting
confidence: 69%
“…The release of NO in the medium was evaluated by Griess assay as previously described (20). In brief, following incubation with nitrate reductase for 1 h at 37˚C, the medium was mixed with an equal volume of Griess reagent (Sigma-Aldrich).…”
Section: Drugsmentioning
confidence: 99%
“…The cycloartane-type saponin molecule found in roots of Astragalus (ASI) is able to inhibit microglia activation, in LPS treated BV2 cells and in an in vivo neuroinflammatory disease model represented by experimental autoimmune encephalomyelitis (EAE) mice. This effect was obtained by inhibition of PI3K and Akt activation, which in turn led to the deactivation of NF-κB, suggesting that ASI modulates PI3K/Akt, acting through glucocorticoid receptors (GRs) as an active ligand [114].…”
Section: Therapeutic Strategies On the Modulation Of Pi3k Signalingmentioning
confidence: 99%
“…A limitation of the present study was that the cause-effect relationship between astragaloside IV and RXRα was not investigated. It has been previously shown that astragaloside IV can bind to glucocorticoid receptor (GR) with a low affinity, modulating the GR-mediated signaling pathway, including dephosphorylation of PI3K, AKT, inhibitor of κB and NF-κB in microglia (78). Astragaloside IV is a natural PPARγ agonist that suppresses the activity of β-secretase 1 and amyloid β (Aβ) levels in SH-SY5Y cells, and reduces neuritic plaque formation and Aβ levels in the brains of APP/PS1 mice, a model of Alzheimer's disease (79).…”
Section: Discussionmentioning
confidence: 99%